GENDER EQUALITY IN THE MODERNISM ERA - Fransiska Novita Eleanora; Andang Sari (Fakultas Hukum Universitas Sriwijaya, 2019)
Discrimination against women is a problem that often occurs in almost all walks of life, even in most parts of the world. The reason is quite clear, patriarchal culture cannot be released by and people who for thousands of years ensnare and force women to always be in the power of Adam, namely men. Not without reason if education is very important for women, because women have a very important role in improving the quality of the younger generation. With this, awareness is needed to increase the quality of education for a woman, given her responsibilities and role as the first and foremost educator. Bringing up a generation from the nation's successor that is naturally due to or caused by emotional closeness to children is a matter of giving birth to a child in the world that is adjusted to its dignity, or even the dignity of women who are not separated from their role and form , and gives color to the quality of the nation and its generation. The purpose of this study is to find out why women are often harmed or there is discrimination in aspects of life and gender equality in the current era of modernization. Research methods use juridical and normative research methods. in the current era of modernization.Keywords: equality; gender; discrimination